Evaluation of serum gamma-glutamyl transferase and highly sensitive C-reactive protein as biomarkers of oxidative stress and inflammation in type 2 diabetes mellitus patients with good and poor glycemic control - Krishnamurthy, Vishwanath; Patted, Arun Sangappa; T., Anil Kumar; Jayaram, Sujatha Kuppuswamy; Magaji, Bhavana Shree (International Journal of Advances in Medicine, 2019)
Background: Diabetes mellitus comprises a group of common metabolic disorders which share common phenotype of hyperglycaemia. Oxidative stress and inflammation are associated with poor glycaemic control and further pathogenesis and complications of diabetes mellitus. This study investigated for correlation of good and poor glycaemic control with these factors. Methods: Subjects selected for the study were divide into three groups, group I control (n=35), group II type 2 diabetes mellitus patients with good glycaemic control (n=35) and group III type 2 diabetes mellitus patients with poor glycaemic control (n=35). Patients complete blood count, random blood sugar, HbA1c, HsCRP and GGT were investigated. These parameters were statistically analysed for correlation between HbA1c with GGT and HbA1c with hsCRP. Results: The mean HbA1c in group I, II and III were found to be 5.17%, 6.54% and 9.23% respectively. It was statistically significant (p=0.01), as according to the criteria defined for study recruitment. Furthermore, mean GGT and hsCRP levels were evaluated; a statistically significant difference in mean GGT levels as well as hsCRP of three different groups were obtained with a p value of 0.02. Correlation between HbA1c and hsCRP was found to positive (R2=0.17, p=0.03). When GGT was compared with HbA1c across the groups, there was a statistically significant correlation (R2= 0.09, p=0.03). Conclusions: Present study established a positive correlation between HbA1c and GGT, HbA1c and hsCRP, indicating increasing oxidative stress and inflammation in patients with poor glycaemic control.